HUBUNGAN POWER OTOT LENGAN BAHU DENGAN HASIL FOREHAND SMASH PADA PERMAINAN BULUTANGKIS SISWA SMP N 8 PEKANBARU - M. Rizki C, M. Rizki C; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Purpose of this research was to determine whether there is a relationship between shoulder arm muscle power and forehand smash results in badminton games for students of SMP N 8 Pekanbaru. This research was carried out by using a correlation research design in correlation research. The researcher chose individuals who had variations in the matter investigated. All group members selected as research subjects were measured on the two types of variables investigated, then calculated to determine the correlation coefficient. The population and sample in this study were 8 students of SMP N 8 Pekanbaru. The instruments in this study were two hand medicine ball put, and forehand smash tests. Data obtained were analyzed using the moment product correlation. Based on the results of research and data processing using statistical research procedures there is a relationship between variable X with variable Y obtained r count = 0.94> r table = 0.754. Thus Ha is accepted, the hypothesis conclusion is accepted at the level ? = 0.05 in other words there is a significant relationship between the power of the shoulder arm muscles with the results of forehand smashes on the student badminton game at SMP N 8 Pekanbaru. Key Words: Shoulder Arm Muscle Power, Forehand Smash